1994
DOI: 10.1007/bf00025217
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and nickel accumulation in rice plants. Effects on mineral nutrition and possible interactions of abscisic and gibberellic acids

Abstract: Rice plants accumulate high quantities of Cd and Ni when grown for 10 days in a medium containing these heavy metals. Accompanying Cd and Ni uptake, a decrease in shoot and root length was observed, though dry matter accumulation was not affected accordingly. Metal treatments also induced a decrease in K, Ca and Mg contents in the plants, particularly in the shoots, indicating that Cd and Ni interfered not only with nutrient uptake but also with nutrient distribution into the different plant parts. Addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(90 citation statements)
references
References 20 publications
6
74
1
3
Order By: Relevance
“…It was reported that nickel toxicity decreased contents of divalent cations (Ca ++ and Mg ++ ) in rice plant [10]. The results obtained in this study belong Zn and macronutrients contents showed correspond with presented literature knowledges.…”
Section: Resultssupporting
confidence: 90%
“…It was reported that nickel toxicity decreased contents of divalent cations (Ca ++ and Mg ++ ) in rice plant [10]. The results obtained in this study belong Zn and macronutrients contents showed correspond with presented literature knowledges.…”
Section: Resultssupporting
confidence: 90%
“…An increase in soil Ni content from 50 to 200 mg/kg soil decreased the contents of Cu and Mg in the caryopses and Mg and Ca in the shoots of T. aestivum (Barsukova and Gamzikova 1999). Rubio and Pandolfini concluded that at high Ni concentrations (about 0.1-1 mM), the contents of macro and micro-nutrients in plant tissues are usually lowered because of disordered absorption and transport (Rubio et al 1994;Pandolfini et al 1992). At the same time, at low Ni concentrations in the environment (10-1 lM), the contents of nutrients did not change and in some cases even increased (Piccini and Malavolta 1992;Barsukova and Gamzikova 1999).…”
Section: Effect On Mineral Nutritionmentioning
confidence: 99%
“…Therefore, Ni may compete with these metals in the absorption and transpiration processes (Kochian 1991;Kupper et al 1996). As a result of competition, Ni at high concentrations may inhibit the absorption of these metals, decreasing their concentration and even leading to their deficiency in plants (Ahmad et al 2007;Van Assche and Glijsters 1990;Rubio et al 1994). Subsequently, this may affect important physiological processes, and ultimately result in toxic effects (Gajewska et al 2006;Gon_alves 2007).…”
Section: Interference With Other Essential Metal Ionsmentioning
confidence: 99%
“…Bioavailability of heavy metals is mainly affected by total content of soil heavy metal, soil chemical and physical properties and plant species (Cheng et al 2006;Rubio et al 1994). In recent years, researchers have focused their attention on the significance of soil types and genotype on the uptake and accumulation of heavy metal in the pot experiment or hydroponic solution (Li et al 2005;Lee et al 1998;Du et al 2005).…”
mentioning
confidence: 99%